Pembinaan Rancang Bangun Filter Air untuk Mengatasi Air Tanah Asindi Desa Tinumpuk Kecamatan Purwosari Kabupaten Bojonegoro - Mushthofa, Mushthofa; Rahmawati, Alfia Nur; Indriani, Yulia; Faqih, Nasyiin (Universitas Nusantara PGRI Kediri, 2025)
The problem of saline and cloudy groundwater quality in Tinumpuk Village, Purwosari District, Bojonegoro Regency, has rendered the government-built clean water distribution system unusable for the community. This community service program aims to provide an appropriate technological solution in the form of training and assistance in the construction of a two-stage groundwater filtration device. The first filter consists of a 550-liter tank filled with natural materials such as palm fiber, activated carbon, silica sand, and zeolite sand. The second filter, a Fiberglass Reinforced Plastic (FRP) tube containing similar filtration media, functions to re-filter the water before distribution. The program involved village officials, youth organizations, and the general public through focus group discussions (FGDs), technical training, and live demonstrations. The results demonstrated increased community knowledge, skills, and awareness of the importance of sustainable groundwater management and water conservation. Testing of the filtration device demonstrated significant improvements in water quality, both visually and organoleptically. This program has had a positive impact on increasing access to clean water, strengthening community participation, and marking the first step toward community-based clean water independence.